Novel recombinant glycosylphosphatidylinositol (GPI)-anchored ADAMTS13 and variants for assessment of anti-ADAMTS13 autoantibodies in patients with thrombotic thrombocytopenic purpura - Li, Dengju; Xiao, Juan; Paessler, Michele; Zheng, X. Long (Thrombosis and Haemostasis, 2011)
Immunoglobulin Gs (IgGs) against ADAMTS13 are major causes of acquired (idiopathic) thrombotic thrombocytopenic purpura (TTP). We report here a novel cell-based assay using glycosylphosphatidylinositol (GPI)-anchored ADAMTS13 or variants expressed on cell membrane for assessment of autoantibodies in patients with TTP. We showed that IgGs from all 26 patients with acquired TTP bound to cells expressing a GPI anchored full-length ADAMTS13 (gFL) and a variant truncated after the spacer domain (gS). Also, IgGs from 25/26 (96.7%) of these TTP patients bound to cells expressing a GPI-anchored C-terminal fragment, TSP1 2–8 plus CUB (gT2C). In contrast, none of the 20 healthy blood donors showed detectable binding of their IgGs to the cells expressing gFL, gS, and gT2C. A moderate, but statistically significant correlation was observed between plasma concentrations of anti-ADAMTS13 IgG and positive cells expressing gFL (r=0.65), gS (r=0.67), and gT2C (r=0.42). These results suggest that the microtiter-plate assay and the cell-based assay may detect differential antigenic epitopes. Moreover, antigens clustered on cell membranes may enhance antibody binding affinity, thereby increasing analytical sensitivity. Finally, our assay was able to determine kinetic changes of plasma levels of anti-ADAMTS13 IgGs in TTP patients during plasma therapy. Together, our findings suggest that the novel cell-based assay may be applicable for rapid identification and mapping of anti-ADAMTS13 autoantibodies in patients with acquired TTP.
Keywords: von Willebrand factor cleaving protease; thrombotic microangio-pathies; diagnostic test; autoantibody